The influence of corporate social responsibility on work engagement: a systematic literature review - Flaig, Hennes (2023)
: In the last two decades CSR research has shifted from macro-level to micro-level CSR. Especially, employee level outcomes, such as work engagement are investigated. More recently, the underlying mechanisms and boundary conditions in this relationship are re searched. Thus, this paper conducts a systematic literature review to synthesize prior research and to contribute to the understanding of the impact of perceived CSR on work engagement. As a result, 20 different mediators and nine different moderators in the relationship have been identified. Among the mediators are organizational identification, organizational commitment, and organizational justice. Among the moderators are moral identity, and collectivism.